Performing bronchoscopy in times of the COVID-19 pandemic: practice atatement from an international expert panel - Luo, Fengming; Darwiche, Kaid; Singh, Suveer; Torrego, Alfonso; Steinfort, Daniel P.; Gasparini, Stefano; Liu, Dan; Zhang, Wei; Fernandez-Bussy, Sebastian; Herth, Felix; Shah, Pallav L. (Respiration, 2020)
These recommendations for physicians who perform bronchoscopy will help to protect those patients (un)-affected by the current COVID-19 pandemic, minimize the risk of transmission, and maintain clinical care for all patients.
Gesehen am 19.10.2020